2014
DOI: 10.1088/0964-1726/23/9/095002
|View full text |Cite
|
Sign up to set email alerts
|

Structural health monitoring feature design by genetic programming

Abstract: Structural health monitoring (SHM) systems provide real-time damage and performance information for civil, aerospace, and other high-capital or life-safety critical structures. Conventional data processing involves pre-processing and extraction of low-dimensional features from in-situ time series measurements. The features are then input to a statistical pattern recognition algorithm to perform the relevant classification or regression task necessary to facilitate decisions by the SHM system. Traditional desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Feature selection based on a genetic algorithm (GA) is proposed in Ref. [70]; however, the results from a demanding feature selection phase are only comparable to an AR model for damage detection in a simple laboratory structure.…”
Section: Introductionmentioning
confidence: 99%
“…Feature selection based on a genetic algorithm (GA) is proposed in Ref. [70]; however, the results from a demanding feature selection phase are only comparable to an AR model for damage detection in a simple laboratory structure.…”
Section: Introductionmentioning
confidence: 99%
“…The damage localization and quantification steps of SHM have for example been carried out by decomposing the Lamb wave signals using a Proper Generalized Decomposition (PGD) algorithm which is then used to train neural networks in a supervised machine learning framework (Borate et al, 2020). Features automatically extracted by means of genetic algorithms and able to handle Lamb waves for SHM problems have been proposed (Harvey and Todd, 2014). Lamb wave data has also been processed using dynamical wavelet fingerprints and has been demonstrated that features extracted from wavelet analysis of Lamb wave signals can be extremely relevant for SHM purposes (Miller and Hinders, 2014;Hinders and Miller, 2020).…”
Section: Introductionmentioning
confidence: 99%